IMPACT OF ADDING NKL AND FERMIPAN YEAST: MICROBIAL POPULATION AND DISCOLORATION OF COCOA BEAN “ASALAN” CHIPS DURING FERMENTATION - Hermiza Mardesci; Ratri Retno Utami; Mulono Apriyanto (Jurnal Industri Hasil Perkebunan, 2023)
The study aims to determine the effect of adding microbes to the fermentation process of "Asalan" cocoa beans on their quality. Three treatments were applied: the first treatment (A0) served as the control without any microbe addition; the second treatment (A1) involved the addition of NKL and fermipan yeasts at the beginning of fermentation; and the third treatment (A2) included the addition of 1% fermipan yeast initially, followed by 1% NKL yeast after 24 hours. Seed discoloration was evaluated using the Cut Test, while microbial populations were analyzed using the Pour Plate Method. The results showed that at 24, 48, and 72 hours of fermentation, treatment A2 had the highest populations of S. cerevisiae (12.55 x 10-7 cfu/g), L. lactis (12.53 x 10-7 cfu/g), and A. aceti (12.13 x 10-7 cfu/g) among the three treatments. The highest percentage of cocoa bean chips (97.01%) was also observed in treatment A2. Based on the findings, it can be concluded that treatment A2 enhances the population growth and induces a brown color change in cocoa beans